PENERAPAN METODE PENEMUAN TERBIMBING DI KELAS VIII SMP - Toni Hidayat; Sri Mulyati; Abd. Qohar (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2017)
This study was a classroom action research which aims to investigate how the implementation of guided discovery learning can improve students’ activeness and attainment in the class VIII of Laboraturium UM Senior High School Malang city. The study subject was Class VIII that consists of 36 students, year 2016/2017. This study consisted of two cycles, and the data was collected from the result of the final test, observation, and interview. Based on the research of cycle I, the students’ activeness with mean scores of the meeting I, II, III was 78.88%, 79%, 86.6% respectively. The students’ activeness on cycle II, the mean scores of analyst meeting V and VI were 89.22% and 92.24% respectively. The result of Mathematics learning was increased, it is shown on the test mean of the cycle I that was achieved by 36 students with the percentage of successful learning 83 %. On the cycle test II, the average of 36 gained 82 (score) with 7.2 increased from the score mean of the cycle I and with classical mastery learning cycle II 88.88%.Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang bertujuan untuk mengetahui bagaimana penerapan metode penemuan terbimbing yang dapat meningkatan keaktifan dan hasil belajar siswa kelas VIII SMP Laboratorium UM Kota Malang. Subjek penelitian ini ialah siswa kelas VIII yang berjumlah 36 siswa tahun pelajaran 2016/2017. Penelitian ini terdiri atas dua siklus dan data dikumpulkan dari hasil tes akhir tindakan, observasi, dan wawancara. Berdasarakan hasil penelitian pada siklus I, keaktifan siswa siswa dengan skor rata-rata pertemuan I, II, III adalah 78,88% 79,%, dan 86,6%. Aktivitas siswa pada siklus II, rata-rata skor pengamat pertemuan V dan VI berturut-turut 89,22 % dan 92,24%. Hasil belajar matematika siswa meningkat, hal ini terlihat bahwa rata-rata tes siklus I yang diperoleh 36 siswa sebesar 74,8 dengan presentase keberhasilan belajar 83,33%. Pada tes siklus II rata-rata nilai menjadi 82 dengan peningkatan sebesar 7,2 dari rata-rata nilai siklus I dan dengan ketuntasan belajar klasikal siklus II 88,88%.